A new era of sustainable transport: An experimental examination on forecasting adoption behavior of EVs among Malaysian consumer - Adnan, N. (Elsevier Ltd, 2017)
The new global era of economy faced obstacle due to carbon emission. The main reason behind this intensification of crises is caused by the transportation sector, as million petroleum based vehicle are waging on the street day and day which initiated carbon emission. The Malaysian government also faced major problem due to this C02 emission. Because Malaysia is considered as major energy efficient nation. With the aim of obstructing these susceptibilities and endorse a more sustainable economy, the main solution is to change from Petroleum-based vehicles by using green vehicle innovation. Using, Electric Vehicles (EVs) have the probable to lessen the carbon emission, gasoline consumption in order to alleviate the environmental problem. Subsequently, the idea of this paper is to scrutinize whether attitudes (ATT) towards EV adoption by integrating three dimensions of attitude along with the theory of planned behavior the study suggests an assimilated model. A sample of 391 respondent has been collected from Malaysia in order to forecast the customer's purchase intention to adopt EV by using the extended theory of planned behavior. The empirical outcome by using PLS investigation exposed the three dimension of attitude have a significant effect to build attitude. Finally, the finding of this survey questionnaire is analyzed by using Smart PLS to perform CFA and SEM. The outcome of this research specifies that ecological significance and individual preference. © 2017 Elsevier Ltd